Ob 90. jubileju akademkinje, zaslužne profesorice dr. Alenke Šelih - Završnik, Aleš (Pravnik, 2023)
At the National Biannual Criminology Conference “Prevention and (In)Justice”, held on 5 October 2023 at the Faculty of Law, University of Ljubljana, we celebrated the 90th birthday of Dr Alenka Šelih, academician, professor emerita, and longtime director and researcher at the Institute of Criminology at the Faculty of Law in Ljubljana. To celebrate this significant occasion, we inaugurated “Alenka Šelih Lectures”, which were delivered by academician Professor Dr Frieder Dünkel from the University of Greifswald, along with Justice Mag Renate Winter, who served as a judge of several international criminal courts. The paper highlights Acad. Alenka Šelih’s efforts to champion the cause of scientific reasoning over the loud voices of influencers and opinion leaders, and the like. Far too often these latter individuals are silent whisperers to public sentiment and legislators while scientifically grounded voices remain overheard. The paper draws attention to the efforts of Acad. Alenka Šelih to join the forces of researchers from Central and Eastern Europe in having their own voice in the international scientific fora. The paper places her international engagements at the forefront of her achievements since her expertise in crime policy, criminal law and the broader field of criminology, as well as her excellent knowledge of several foreign languages, led to her first appearances abroad in the 1970s and left a remarkable legacy on the development of juvenile justice within the framework of the Council of Europe and the UN.
Keywords: akademiki; biografije; jubileji; kriminologija; pravo; slovenske pravnice; Šelih, Alenka